How did I Become a Researcher? (2016)
Carlos Mario Correa, the last journalist of El Espectador in Medellin tells how he came to journalism, the difficult moments he lived in the newspaper and how he came to the academy to be an investigator in search of giving narrative journalism the position he deserves and to train future generations.